2012
DOI: 10.1260/1750-9548.6.3.267
|View full text |Cite
|
Sign up to set email alerts
|

Shock wave focusing in water inside convergent structures

Abstract: Experiments on shock focusing in water-filled convergent structures have been performed. A shock wave in water is generated by means of a projectile, launched from a gas gun, which impacts a water-filled convergent structure. Two types of structures have been tested; a bulk material and a thin shell structure. The geometric shape of the convergent structures is given by a logarithmic spiral, and this particular shape is chosen because it maximizes the amount of energy reaching the focal region. High-speed schl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…The gas gun and the visualization system have been presented with details elsewhere [6], and will be only briefly introduced here. The gas gun with a 1.8 m long and 0.05 m diameter barrel is used to launch cylindrical projectiles onto the experimental specimen.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…The gas gun and the visualization system have been presented with details elsewhere [6], and will be only briefly introduced here. The gas gun with a 1.8 m long and 0.05 m diameter barrel is used to launch cylindrical projectiles onto the experimental specimen.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…The underwater shock waves in this study are generated using the same experimental setup and technique as reported in our earlier studies (Wang and Eliasson, 2012;Wang et al, 2014). A shock wave in the convergent water-filled section of the specimen is generated by a projectile launched from a gas gun.…”
Section: Methodsmentioning
confidence: 99%
“…High temporal resolution was obtained using a z-folded schlieren setup (Wang & Eliasson 2012) with a high-speed camera (Phantom V711) and a high-power lightemitting diode (Cree XLamp, XP-G2 LEDs, Cool white). Schlieren visualization was used instead of shadowgraph to avoid any inherent ambiguity from the shadow images.…”
Section: Schlieren Visualization With High Temporal Resolutionmentioning
confidence: 99%